Edebiyat Tarihimize Işık Tutan Bir Eser: Ata Tarihinin 4-5. Ciltleri - Eliaçık, Muhittin (Gökkubbe, 2005)
19 yüzyıl divan şairlerinden olan Tayyarzade Atâ Bey Enderun tarihi nitelığindeki tarih kitabıyla bilinir. Bu eserinin Enderun şairlerini anlatıp şiirlerinden örnekler verdiği 4. ve 5. ciltleri edebiyat tarihimiz için çok önemlidir. Bu makalede Ata Tarihinin 4-5.ciltlerinde gösterilmiş olan Enderunlu şairler incelenip araştırılacaktır. The 19th century Ottoman poet Tayyarzade Ata Bey is known with his history of the poets serving as servant in the Ottoman Palace. The fourth and fifth volumes of Ata's history are on servant poets of the Palace. Therefore these volumes are very important for Turkish literary history. In this article, the poets included in the fourth and fifth volumes of Ata's history is examined and discussed.
A Work that Sheds Light on Our Literary History: Fourth and Fifth Volumes of Ata History
Keywords: Ata Tarihi; Enderun Şairleri; Eski Türk Edebiyatı; Ata's History; Old Turkish Literature; Enderun Poets; Private Court